Rancang Bangun Aplikasi TPS Berbasis Android - Sandhi, Bagus Hari; Purnama, Iwan (Jurnal Gemilang Informatika (GIT), 2024)
The design and development of a Polling Station Application based on Android Studio represent an innovative step in crafting a more efficient electoral process. This application is designed to enhance data readability and security, facilitating the execution of general elections. An intuitive interface simplifies voter registration, vote recording, and real-time result viewing. The utilization of Android Studio not only provides technical stability but also enables real-time result reporting. With this feature, the application can help reduce the potential for fraud and expedite the announcement of election results. Furthermore, careful data analysis can offer a more accurate portrayal of voter preferences. Through the adoption of this technology, it is anticipated that voter participation will increase, strengthening the integrity of democracy and ensuring a more transparent and effective representation of the people's will in general elections. Thus, this application serves as a progressive solution in supporting modern democratic systems.